Characterization of children younger than 5 Years of age with severe community-acquired alveolar pneumonia (CAAP) requiring Pediatric Intensive Care Unit (PICU) admission - Yael Feinstein; David Greenberg; Shalom Ben-Shimol; Maya Mimran; Ron Dagan; Noga Givon-Lavi (Elsevier, 2020)
Background: The purpose of this study was to determine factors characterizing children admitted to the Pediatric Intensive Care Unit (PICU) with community-acquired alveolar pneumonia (CAAP) to help clinicians assess disease severity upon initial assessment in the emergency department. Methods: We prospectively collected demographic, clinical, and laboratory data of children <5 years with radiologically confirmed CAAP referred to the Soroka University Medical Center during 2001-2011. Three groups of children were compared: 1) those hospitalized in the PICU (PICU-CAAP); 2) those treated in the emergency department and discharged (ED-CAAP); and 3) those hospitalized in a pediatric ward (Hosp-CAAP). Results: Of 9722 CAAP episodes, 367 (3.8%) were PICU-CAAP, 5552 (57.1%) Hosp-CAAP and 3803 (39.1%) ED-CAAP. In a univariate analysis, respiratory syncytial virus (RSV) was detected more commonly among PICU-CAAP than in Hosp-CAAP (P = 0.02) and ED-CAAP patients (P < 0.001). In a multivariate analysis, several factors were associated with PICU hospitalization versus ED-CAAP and Hosp-CAAP: Younger age (ORs: 1.04, [95%CI: 1.02-1.05] and 0.97 [0.96-0.98], respectively); prematurity (ORs: 2.16 [1.28-3.64] and 1.61 [1.15-2.26], respectively), lower O2 saturation (ORs: 1.32 [1.25-1.41] and 0.94[0.92-0.96]), higher respiratory rate (ORs: 1.06 [1.04-1.07] and 1.00 [1-1.01], respectively). Conclusion: Children admitted to PICU were younger, had more respiratory syncytial virus (RSV) detection, were premature, had lower O2 saturation, and had a higher respiratory rate than those admitted to the general ward or those visiting the emergency department and subsequently discharged.